Perencanaan Konsep Desain Daur Ulang Plastik Untuk Bahan Bangunan - Indah Yulia Sari; Bambang Perkasa Alam; Wiyoga Triharto (Universitas Indraprasta PGRI, 2022)
The purpose of community service is for residents to have skills in planning plastic recycling designs into items of economic value as an alternative to building materials and have an entrepreneurial spirit. The method used is observation, interviews, and training. Based on the training that has been carried out, the following results are obtained: 1. Residents are able to process other recycled plastic materials with various functional process design concepts. 2. Residents are able to create attractive design concepts in the marketing phase of building materials. 3. Residents are able to market plastic recycling designs through social media and marketplaces as alternative activities for online entrepreneurship.